Pengaruh Promosi dan Citra Merek terhadap Keputusan Pembelian Susu UHT Indomilk: Studi pada Konsumen Susu UHT Indomilk di Surabaya - Nurbayzura, Wahyu; Soebiantoro, Ugy (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The demand for packaged soft drinks has increased significantly, this phenomenon of brand competition can be seen through packaged milk products, especially UHT milk. The demand for UHT dairy products is increasing along with the increase in people's income and public awareness of health. The purpose of this study was to determine the effect of promotion and brand image on purchasing decisions. Promotions (X1), brand image (X2), and purchasing decisions (Y) are the variables in this study.. The population in this study were consumers of Indomilk UHT milk in Surabaya with a total sample of 108 respondents. The sampling method is non-probability sampling with purposive sampling techniques. The Partial Least Square (PLS) analysis tool is used in data analysis techniques. The results of the study stated that promotion and brand image had a positive and significant effect on purchasing decisions.